The Use Of Circle Games To Improve The Students’ Mastery In Vocabulary - Elisa Usfal; Napitupulu, Merlin Helentina; Thresia Trivict Semiun (Jurnal Pendidikan LLDIKTI Wilayah 1 (JUDIK), 2025)
Mastery of English vocabulary is essential for students to develop their language skills, particularly in reading, writing, listening, and speaking. However, many students at SMPN Satap Heututan have shown limited vocabulary knowledge, which affects their overall English proficiency. This research aimed to improve students' vocabulary mastery through the use of circle games during the academic year 2024/2025. The study employed a pre-experimental design consisting of three stages: pre-test, treatment, and post-test. The data were quantitative, collected from 20 seventh-grade students as research participants. Two types of test instruments—multiple-choice and noun identification—were used in both the pre-test and post-test. The results demonstrated that the application of circle games significantly improved students’ vocabulary skills. The mean score increased from 48.75 in the pre-test to 80.25 in the post-test, resulting in a gain of 31.5 points. This improvement is considered significant, indicating a notable enhancement in vocabulary mastery after the treatment. Additionally, the use of circle games created a more engaging and interactive classroom environment. Students were more active, motivated, and responsive, showing greater interest and attention during the learning process. In conclusion, the implementation of circle games is an effective and enjoyable strategy for enhancing vocabulary acquisition among seventh-grade students at SMPN Satap Heututan.